2023
DOI: 10.3389/fpls.2023.1091875
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis for drought tolerance and associated traits in faba bean (Vicia faba L.)

Abstract: Faba bean (Vicia faba L.) is an important high protein legume adapted to diverse climatic conditions with multiple benefits for the overall sustainability of the cropping systems. Plant-based protein demand is being expanded and faba bean is a good candidate to cover this need. However, the crop is very sensitive to abiotic stresses, especially drought, which severely affects faba bean yield and development worldwide. Therefore, identifying genes associated with drought stress tolerance is a major challenge in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 94 publications
(107 reference statements)
4
8
0
Order By: Relevance
“…The latter accession was also recorded as producing the most stems in this study; therefore, seed production may have been sacrificed for vegetative growth. Seed number per pod was moderately heritable with a broad‐sense heritability of 55%, which is consistent with the result of a previous study 63 where it was reported as 62%.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The latter accession was also recorded as producing the most stems in this study; therefore, seed production may have been sacrificed for vegetative growth. Seed number per pod was moderately heritable with a broad‐sense heritability of 55%, which is consistent with the result of a previous study 63 where it was reported as 62%.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, 100-seed weight was negatively correlated with seed shape (r = À0.69, p < 0.01) indicating that rounder seeds are often smaller than flattened seeds (Table S7). Broadsense heritability for 100-seed weight was previously reported as 66% 63 and 99%, 37 which is consistent with our work (89%). These results indicate that direct selection based on mean weight would be an effective way to improve this trait.…”
Section: Quantitative Characteristicssupporting
confidence: 93%
See 3 more Smart Citations